Proses Pemecahan Masalah Siswa Menengah Pertama dalam Menyelesaikan Masalah Lingkaran - Novita Erni Hendrawati; Elly Susanti; Turmudi Turmudi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
Problem-solving abilities have an important role in learning, especially in solving math problems, one of which is in circle material. This study aims to describe the mathematics problem solving process of junior high school students in solving circle problems through the process of solving problems in IDEAL. The approach used is a qualitative approach with a descriptive type. The sampling technique used in this research is purposive sampling technique. The results showed that, based on the problem-solving process, each subject had a different problem-solving process. S-1 with the category of completely solving problems fulfills the indicators in solving IDEAL problems. S-2 with the category of correct but not perfect does not yet fulfill the IDEAL problem-solving process. S-2 experienced errors when exploring the strategy and implementing the first problem strategy so that the final result was not in accordance with the objectives of the first problem. S-3 with the category of imperfect does not yet fulfill the IDEAL problem-solving process. S-3 only fulfills one IDEAL problem solving indicators, implementing strategies. However, the problem-solving process carried out by S-3 is not exactly in accordance with the objectives of the first and second problems.